La Pedagogía Waldorf para el desarrollo de la creatividad en los niños de inicial II de la Unidad Educativa Yaruquíes en la cuidad de Riobamba provincia Chimborazo período 2021 - Trujillo Chávez, Dayana Andrea (2022)
The proposed topic on the Waldorf pedagogy for the development of creativity in children of kindergarten II of the Yaruquíes Educational Unit in the city of Riobamba, province of Chimborazo, period 2021, has the objective of establishing the importance of the Waldorf pedagogy for the development of creativity in children. This pedagogy is based on free instruction and starts from each child's interests to form autonomous and capable beings so that they develop all their abilities and skills throughout the teaching-learning process. Methodologically, this research has a qualitative approach since a description of the observable reality is made regarding the creative manifestation of the children when working under Waldorf pedagogy. The inductive method was applied since an analysis of particular situations of the children is made to make later a generalization about the results obtained. A survey directed to parents was used to gather information regarding creativity. On the other hand, to measure the development of creativity in children, the Torrance test was applied to which adaptations were made to create a drawing from a given form and represent a situation. First, a worksheet was used without putting Waldorf pedagogy into practice, and then another one applied the pedagogy. The results obtained in the present investigation are favorable since it was possible to confirm that Waldorf pedagogy significantly influences the development of the child's creativity.